2021
DOI: 10.1016/j.ultsonch.2021.105508
|View full text |Cite
|
Sign up to set email alerts
|

Optimized sonoreactor for accelerative amyloid-fibril assays through enhancement of primary nucleation and fragmentation

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 49 publications
(43 reference statements)
0
35
0
Order By: Relevance
“…S1 ). First, we monitored the kinetics of fibril amplification by our HANABI assay 30,31 ( Figure 1.A ), an instrument that consists of an optimized sonoreactor equipment developed by our group, that applies ultrasonic irradiation pulses individually to each one of the wells of a 96-wells microplate, and records the ThT fluorescence in function of time, named HANABI-2000 31 . This instrument accelerates substantially the rate of fibril formation reaction compared with the traditional RT-QuIC methods 32,33 , from several days to a few hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 ). First, we monitored the kinetics of fibril amplification by our HANABI assay 30,31 ( Figure 1.A ), an instrument that consists of an optimized sonoreactor equipment developed by our group, that applies ultrasonic irradiation pulses individually to each one of the wells of a 96-wells microplate, and records the ThT fluorescence in function of time, named HANABI-2000 31 . This instrument accelerates substantially the rate of fibril formation reaction compared with the traditional RT-QuIC methods 32,33 , from several days to a few hours.…”
Section: Resultsmentioning
confidence: 99%
“…The ThT fluorescence intensity was monitored using a HANdai Amyloid Burst Inducer (HANABI-2000) equipment, developed by our group in collaboration with CORONA ELECTRIC, Ibaraki, Japan, consisting of a transducer driving system, an acoustic-intensity measurement system, and a fluorescence measure system, in which a microplate reader was combined with a multichannel ultrasonication system that applies ultrasonic irradiation independently to each individual well of the microplate via a miniaturized ultrasonic resonator attached to each well. Ultrasonication was applied to accelerate amyloid formation at an optimized frequency of 30 kHz 31,47 in cycles of 300 ms of irradiation and 500 ms of quiescence. The kinetic parameters of fibril formation was determined by fitting the experimental data to empirical equations 48 .…”
Section: Kinetics Of Fibril Formation Followed By Thioflavin T (Tht)mentioning
confidence: 99%
“…Thus, control reactions were performed at 1.0 mg/mL 2m at pH 7.4 and 60 °C. To apply further effective agitation to induce amyloid fibril formation, we adopted an originally developed ultrasonic instrument, HANABI-2000 [27][28][29] , which accelerates amyloid fibril formation 10,11,31,32 by the effects of ultrasonic cavitation 33,34 and monitors amyloid formation by amyloid-specific fluorescence dye, thioflavin-T (ThT) 35 . Scheme of the experiment is described in Figure S2.…”
Section: Hanabi Assay For 2m Amyloid Fibril Formationmentioning
confidence: 99%
“…It should be noted that, although previous studies [23][24][25][26] investigated amyloid fibril formation in a crowded milieux (e.g., serum milieu), there is no consensus on the effects of macromolecular crowding in a serum milieux. With HANABI-2000 [27][28][29] , an ultrasonication-forced amyloid fibril inducer, the effects of sera from hemodialysis patients on 2m amyloid fibril formation were investigated. To perform a systematic investigation, we collected over 100 sera from individuals with or without hemodialysis therapy.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we successfully detected the amyloid fibril formation of β2-microglobulin (β2m) and the low concentration seed of β2m. 37,38 We name this improved HANABI system "HANABI-2000". In the previous study, 36 we have shown that the developed multichannel ultrasound reactor is capable of inducing fibrillation reactions of Aβ 1−40 and αsynuclein solutions.…”
Section: Introductionmentioning
confidence: 99%